Democratization as a Catalyst for Women Empowerment: A Feminist of Reading of Nadine Gordimer’s None to Accompany Me - Malesela Edward Montle (Institut Agama Islam Negeri Palopo, 2022)
This paper aims to explore the role of democratisation in the socio-economic and political empowerment of women from various walks of life. Women were and are still one of the marginalised groups in the globe. Prior to democratisation, women’s authentic voices and identities were abridged to subservience and their societal roles were, predominately, pinned to domesticity whereas their male counterparts relished in administrative dominance. It is the advent of the democratic jurisdiction that occasioned and championed equality amongst men and women in socio-economic and political spaces. This democratisation authorised and empowered women to assert and reassert their identities, which are, sometimes, questioned, berated and shunned despite the autonomous dispensation. This is evinced by the appalling patriarchal, sexist and misogynistic attitudes that menace the women’s rise and impact in society in the present day. The paper employs a qualitative method guided by textual analysis to probe into democratisation as a catalyst for women empowerment from a literary perspective. It selects and utilises Nadine Gordimer’s None to Accompany Me as a case in point to crystalise the focal theme of the study. Furthermore, the study scrutinises Gordimer’s literary work above, which is a reflection of democratisation as an impulse for women empowerment with a feminist lens. This paper, among other things, finds that whilst democratisation has aided and granted women rights to create a platform to authenticate their voices and reconstruct their identities, it has not utterly liberated the women from socio-economic and political maladies.